2011
DOI: 10.1166/jbt.2011.1005
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Nanocomposite Hydrogels: Transparency, Rapid Deswelling and Cell Release

Abstract: Thermal modulation reversibly switches poly(N-isopropylacrylamide) (PNIPAAm) hydrogels between a water-swollen and a deswollen state which is useful for a variety of biomedical applications. The utility and efficiency of PNIPAAm hydrogels requires tailoring their rate of deswelling/reswelling, mechanical properties and/or optical clarity. In the current work, we prepared novel thermoresponsive nanocomposite hydrogels comprised of a PNIPAAm hydrogel matrix and polysiloxane colloidal nanoparticles (~54 nm ave. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…This effect was similarly observed when ~50 and 200 nm polysiloxane nanoparticles were incorporated into SN hydrogels. 51,52 The lack of change to the VPTT is attributed to the discrete nature of the nanoparticles which apparently do not interfere with dissociation of water molecules around the PNIPAAm propyl moieties during heating.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was similarly observed when ~50 and 200 nm polysiloxane nanoparticles were incorporated into SN hydrogels. 51,52 The lack of change to the VPTT is attributed to the discrete nature of the nanoparticles which apparently do not interfere with dissociation of water molecules around the PNIPAAm propyl moieties during heating.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we also observed that nanocomposite hydrogels containing ~50 nm particles exhibited an exceptionally enhanced rate of deswelling. 51 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most significant factors for transparency is the microstructure that includes micelle size, micellar boundaries (amorphous regions between adjacent micelles), crystallization of micelles structure, pore size, and least contamination. [56][57][58][59] It has been hypothesized that the polymer concentration affects micellar morphology, 60,61 which indeed influences light transmittance. At high enough concentrations, the self-assembled nanocomplexes can order themselves in much the same way as lyotropic liquid crystals do.…”
Section: Light Transmittancementioning
confidence: 99%
“…The interactions between organic polymers and nanomaterials for the NC hydrogel formation and their application in biomedicine have been investigated in several reports (please see refs …”
Section: Nanocomposite Hydrogels Of Nanomaterials As Biomaterialsmentioning
confidence: 99%